Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/14786419.2013.821119
|View full text |Cite
|
Sign up to set email alerts
|

A new quassinoid from fruits of Brucea javanica

Abstract: A new minor quassinoid named bruceine M (1), together with 12 known quassinoids (2-13), was isolated from the fruits of Brucea javanica (Simaroubaceae). Their structures were determined by interpretation of NMR and HR-ESI-MS data. The structures of the known compounds were confirmed by comparison of their spectral data with those reported in the literatures. In vitro cytotoxicity of the isolated compounds against cancer cell lines Bel-7404, MCF-7 and A549 was evaluated. Compounds 4, 6 and 9 exhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…javanica fruit and seed-derived extracts or commercially available oil emulsion have been investigated. (8,9,(11)(12)(13)(14)(15)(16) Currently, we investigated on BJLE as another possible potential source for anti-cancer agent. We found that treatment of BJLE reduced cell viability percentages in BJLE concentration dependent manner.…”
Section: Bjle Attenuated Mitochondrial Membrane Permeability (Mmp)mentioning
confidence: 99%
See 3 more Smart Citations
“…javanica fruit and seed-derived extracts or commercially available oil emulsion have been investigated. (8,9,(11)(12)(13)(14)(15)(16) Currently, we investigated on BJLE as another possible potential source for anti-cancer agent. We found that treatment of BJLE reduced cell viability percentages in BJLE concentration dependent manner.…”
Section: Bjle Attenuated Mitochondrial Membrane Permeability (Mmp)mentioning
confidence: 99%
“…(3)(4)(5)(6)(7) B. javanica extract has been reported to have antiproliferative and cell death induction activities. (8)(9)(10)(11)(12)(13)(14)(15)(16) There were numerous cancer lines have been tested with B. javanica extract, including breast cancer cell lines, such as MCF-7 (8-10), HTB126 (9) and MDA-MB231 (11); cervical cancer cell lines, such as CaSki (9), C33A (9) and HeLa (9); pancreatic cancer cell lines, such as PANC-1 (12,13), SW1990 (12,13), CAPAN-1 (12,13) and CAPAN-2 (14); non-small cell lung cancer cell line, such as A549 (8,11); prostate cancer cell line, such as LNCaP (9); hepatic cancer cell line, such as Hep3B (11); oesophageal cancer cell line, such as SLMT-1 (11); bladder cancer cell line, such as T24 (15); colon cancer cell line, such as HCT116 (16); oral cancer cell lines, such as KB (17) and ORL-48 (17). All reports showed that B. javanica extract was cytotoxic for cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, far, 72 compounds have been identified from these plants, including 52 quassinoids, nine triterpenoids, five glycosides and one monoterpenoid (Liu et al, 2011). Bruceine A is isolated from the seeds and fruit of B. javanica (L.) Merr (Kim et al, 2004;Liu et al, 2012;Su et al, 2013;Ye et al, 2015;Du et al, 2017) and has the molecular formula C 26 H 34 O 11 , a mass of 522.54 g/mol and a powder with bitter taste (NoorShahida et al, 2009;Liu et al, 2011). Bruceine A has insecticidal, antifeedant and growth inhibition activities against tobacco budworm (Heliothis virescens F), armyworm (Spodoptera frugiperda) (Klocke et al, 1985) and fourth instar larvae of Mexican beetles (Epilachna varivestis Mulsant) (Leskinen et al, 1984).…”
Section: Introductionmentioning
confidence: 99%